Connected strategy : building continuous customer relationships for competitive advantage - Siggelkow, Nicolaj, (Harvard Business Review Press, 2019)
The Internet of Things, robo investment advisers, wearable fitness devices, remote health care operations . . . business executives in many industries are currently being inundated with a confusingly and exhaustingly broad range of technological developments that enable new business models. There is, however, a common thread among all of these developments: firms are fundamentally changing how they connect with their customers. Rather than having occasional, episodic interactions--where customers realize they have an unmet need and then look for ways to fill it--firms are striving to be continuously connected to their customers, providing services and products as the needs arise, even before customers become aware of them. Firms such as Nike, Disney, Progressive Insurance, McGraw-Hill Higher Education, Medtronic, Hewlett-Packard, and Tesco are developing and competing on connected strategies: creating superior customer experiences through connectivity while simultaneously driving dramatic improvements in operational efficiencies and reshaping their industries. Strategy and operations experts Nicolaj Siggelkow and Christian Terwiesch reveal the emergence of connected strategies across a broad array of industries and show how these strategies work, how they eliminate the trade-off between superior customer experience and low cost, and how companies can formulate, design, and implement them. In showing how to create a connected strategy, the authors reveal the four pathways--respond-to-desire, curated offerings, coaching, and automatic execution--for turning occasional, episodic interactions into continuous relationships. Siggelkow and Terwiesch show you how to:--